P50 suppresses cytotoxic T lymphocyte effector function to regulate tumor immune escape and response to immunotherapy. Issue 2 (13th October 2020) - Lu, Chunwan; Klement, John D; Smith, Alyssa D; Yang, Dafeng; Waller, Jennifer L; Browning, Darren D; Munn, David H; Liu, Kebin
Abstract : Background: NF-κB is a key link between inflammation and cancer. Previous studies of NF-κB have largely focused on tumor cells, and the intrinsic function of NF-κB in T cells in tumor development and response to immunotherapy is largely unknown. We aimed at testing the hypothesis that NF-κB1 (p50) activation in T cells underlies human colon cancer immune escape and human cancer non-response to anti-PD-1 immunotherapy. Methods: We screened NF-κB activation in human colon carcinoma and used mouse models to determine p50 function in tumor cells and immune cells. RNA-Seq was used to identify p50 target genes. p50 binding to target gene promoters were determined by electrophoresis mobility shift assay and chromatin immunoprecipitation. A p50 activation score was generated from gene expression profiling and used to link p50 activation to T-cell activation and function pre-nivolumab and post-nivolumab immunotherapy in human patients with cancer. Results: p50 is the dominant form of NF-κB that is highly activated in immune cells in the human colorectal carcinoma microenvironment and neighboring non-neoplastic colon epithelial cells. Tumor cell intrinsic p50 signaling and T-cell intrinsic p50 signaling exert opposing functions in tumor growth control in vivo. Deleting Nfkb1 in tumor cells increased whereas in T cells decreased tumor growth in preclinical mouse models. Gene expression profiling identified Gzmb as a p50 target in T cells. p50 binds directly to a previously uncharacterized κB sequence at the Gzmb promoter in T cells, resulting in repression of Gzmb expression in tumor-infiltrating cytotoxic T lymphocytes (CTLs) to induce a dysfunctional CTL phenotype to promote tumor immune escape. p50 activation is inversely correlated with both GZMB expression and T-cell tumor infiltration in human colorectal carcinoma. Furthermore, nivolumab immunotherapy decreased p50 activation and increased GZMB expression in human patients with melanoma. Conclusions: Inflammation activates p50 that binds to the Gzmb promoter to repress granzyme B expression in T cells, resulting in CTL dysfunction to confer tumor immune escape and decreased response to anti-PD-1 immunotherapy.